PENINGKATAN STRATEGI PEMASARAN UMKM YOFI FISH GUNA MENINGKATKAN KEUNGGULAN BERSAING - Elsamia Ramadhani Juairiyah; Susanti Dwi Ilhami; Syaiko Rosyidi; Angelina Salsa Faradilla; Ahmad Saiful Ade Prayoga (CV. Denasya Smart Publisher, 2025)
Business Work Lecture (KKU) is one of the community service programs implemented by students as part of the higher education curriculum. The target of this activity is 1 business actor, namely Mr. Yokim, the owner of the Yofi Fish business, an MSME who needs help to develop his business. The purpose of this activity is to help develop his business in terms of marketing and branding. The community service activity (KKU) carried out by YPPI Rembang University Students together with the Supervisor provides assistance to MSME actors. Especially the Yofi Fish MSME which is one of the business actors in the field of catfish cultivation and processing which is facing increasingly tight market competition. The results show that optimizing marketing strategies, especially through improving product quality, adjusting competitive prices, wider distribution, and utilizing social media and digital promotions, can increase the competitiveness of the Yofi Fish MSME. The owner of the MSME, Mr. Yokim, feels very helped and very satisfied with the program. To expand the distribution network of MSME products more effectively, namely through marketing strategies using social media WhatsApp and Facebook.